Income tax reform to relieve middle income households - Stefan Bach; Hermann Buslei (DIW Economic Bulletin, 2017)
Completely eliminating the sharp rise in the tax rate for middle income households in Germany by changing personal income tax rates would mean estimated annual losses in tax revenue of 35 billion euros, or 1.1 percent of GDP. Taxpayers with high incomes would also benefit from this type of relief. The ten percent of the population with the highest income would have a relief of around 10.4 billion euros-over 2,000 euros per taxpayer on average- while middle income taxpayers would benefit to a much lesser extent. With regard to tax burdens or taxable income, the middle and higher income segments would experience more relief than the highest income segment. If high tax revenue losses ought to be avoided and the relief to be focused on middle income taxpayers, tax rates in the upper income segments must be raised. A moderate increase in maximum tax rates would only result in limited extra revenue.
Keywords: H24; H22; D31; 330; personal income taxation; tax burden and distribution; tax revenue